2013
DOI: 10.12816/0000604
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Iron Status in Anemic Children with Chronic Kidney Disease

Abstract: Background: Iron deficiency is the commonest cause of resistance to erythropoiesis stimulating agents (ESAs) in dialyzed children treated from anemia of chronic kidney disease (CKD). Aim of the work: This study was conducted in order to evaluate the significance of different biomarkers in assessment of iron status during management of anemic children with CKD. Patients and method: Twenty five children with diagnosis of anemia of chronic kidney disease were enrolled for the study. They were classified into two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
0
0
Order By: Relevance
“…Furthermore, Venkatesan et al [13] found that there were substantial variations in the study groups' Hb levels and anaemia severity. According to Alzahrani et al [14] , prior to therapy, hemodialysis patients' RBC indices [RBCs counts, haemoglobin, HCT%, and MCH] all showed a substantial decline when contrasted with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Venkatesan et al [13] found that there were substantial variations in the study groups' Hb levels and anaemia severity. According to Alzahrani et al [14] , prior to therapy, hemodialysis patients' RBC indices [RBCs counts, haemoglobin, HCT%, and MCH] all showed a substantial decline when contrasted with the control group.…”
Section: Discussionmentioning
confidence: 99%